Diversity, antibacterial and phytotoxic activities of actinomycetes associated with Periplaneta fuliginosa - Qihua Liu; Jian Tao; Longhui Kan; Yinglao Zhang; Shuxiang Zhang (PeerJ)
Background Insect-associated actinomycetes represent a potentially rich source for discovering bioactive metabolites. However, the diversity, antibacterial and phytotoxic activities of symbiotic actinomycetes associated with Periplaneta fuliginosa have not yet been conducted. Results A total of 86 strains of actinomycetes were isolated from the cornicles and intestines of both nymphs and adults of P. fuliginosa. Diversity analysis revealed that the isolated strains were preliminarily identified as 17 species from two genera, and the dominant genus was Streptomyces. A total of 36 crude extracts (60%) obtained from the supernatant of the 60 fermented strains exhibited a potent antibacterial activity against at least one tested pathogenic bacterium. Among these active strains, 27 crude extracts (75%) exhibited phytotoxic activity against the radicle of Echinochloa crusgalli. Furthermore, seven known compounds, including methoxynicotine (1), (3Z,6Z)-3-(4-methoxybenzylidene)-6-(2-methylpropyl) piperazine-2,5-dione (2), XR334 (3), 1-hydroxy-4-methoxy-2-naphthoic acid (4), nocapyrone A (5), β-daucosterol (6), and β-sitosterol (7) were isolated from an active rare actinomycete Nocardiopsis sp. ZLC-87 which was isolated from the gut of adult P. fuliginosa. Among them, compound 4 exhibited moderate antibacterial activity against Micrococcus tetragenus, Staphylococcus aureus, Escherichia coli, and Pseudomonas syringae pv. actinidiae with the zone of inhibition (ZOI) of 14.5, 12.0, 12.5, and 13.0 mm at a concentration of 30 μg/disc, respectively, which was weaker than those of gentamicin sulfate (ZOI of 29.5, 19.0, 18.5, and 24.5 mm). In addition, the compound 4 had potent phytotoxic activity against the radicle of E. crusgalli and Abutilon theophrasti with the inhibition rate of 65.25% and 92.68% at the concentration of 100 μg/mL. Conclusion Based on these findings, this study showed that P. fuliginosa-associated actinomycetes held promise for the development of new antibiotic and herbicide resources.